2003
DOI: 10.1046/j.1460-9568.2003.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Enriched environment and physical activity stimulate hippocampal but not olfactory bulb neurogenesis

Abstract: Exposure to an enriched environment and physical activity, such as voluntary running, increases neurogenesis of granule cells in the dentate gyrus of adult mice. These stimuli are also known to improve performance in hippocampus-dependent learning tasks, but it is unclear whether their effects on neurogenesis are exclusive to the hippocampal formation. In this study, we housed adult mice under three conditions (enriched environment, voluntary wheel running and standard housing), and analysed proliferation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
470
6
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 699 publications
(522 citation statements)
references
References 35 publications
20
470
6
17
Order By: Relevance
“…This finding is in general agreement with several previous studies that have demonstrated that EE can increase neural progenitors in the hippocampus [6,7,16,22,54,79,81]. However, this finding was also novel and somewhat unexpected in comparison to previous studies because 1) in intact animals, EE produced bilateral increases in neural progenitors in the granule cell layer, and no increases in the hilus [6,54,81], and 2) following an ischemic injury, two weeks of EE did not have an additive effect on the number of progenitor cells in the dentate gyrus [5]. There are several possible explanations for the differences between our findings and those of previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in general agreement with several previous studies that have demonstrated that EE can increase neural progenitors in the hippocampus [6,7,16,22,54,79,81]. However, this finding was also novel and somewhat unexpected in comparison to previous studies because 1) in intact animals, EE produced bilateral increases in neural progenitors in the granule cell layer, and no increases in the hilus [6,54,81], and 2) following an ischemic injury, two weeks of EE did not have an additive effect on the number of progenitor cells in the dentate gyrus [5]. There are several possible explanations for the differences between our findings and those of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike the BrdU data, which demonstrated increased survival of cells that were proliferating at the time of injury, the ki67 labeling did not differ between groups or sides of the brain. These findings are in agreement with previous studies where EE was demonstrated to increase cell survival, but not ongoing proliferation in control animals [6,9,43,54,73,81]. Interestingly, running increases both cell proliferation and survival of progenitors in the dentate gyrus [16], which underscores the importance of clarifying how specific components of these behavioral interventions can differentially modulate progenitor cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results demonstrate that input from ipsilateral olfactory structures plays a role in hippocampal dentate cell death, in addition to the roles previously demonstrated for exploration and learning [9,25], exercise [4,6,28] and hormones and stress [20]. The fact that the effects were limited to the ipsilateral hemisphere in unilateral OBX animals argues against a generalized or widespread system degeneration.…”
Section: Discussionsupporting
confidence: 61%
“…Two regions uniformly agreed to display continual neurogenesis through life are the olfactory bulb and the hippocampal dentate gyrus [1,2,15,18]. In both structures, survival of adult generated neurons is dependent on their being incorporated into an active circuit [4,9,18,23]. For example, exposure to specific odors enhances the survival of adult-born granule cells within spatial regions of the olfactory bulb activated by those odors [23].…”
Section: Introductionmentioning
confidence: 99%